Temporal Dynamics of Rhizosphere Communities Across the Life Cycle of Panax notoginseng - Wei, Guangfei; Li, Mengzhi; Zhang, Guozhuang; Chen, Zhongjian; Wei, Fugang; Jiao, Shuo; Qian, Jun; Wang, Yong; Wei, Jianhe; Wang, Yitao; Meng, Xiangxiao; Fitzgerald, Martin; et al. (Frontiers in Microbiology, 2022)
Rhizosphere microbiome plays important roles in promoting plant growth. How rhizosphere microbial community experiences succession during perennial medicinal plants Panax notoginseng growth stages, however, is still unclear. Here, amplicon sequencing was performed to assess the succession characteristics of rhizosphere microbiomes during developmental stages. The results showed that bacterial and fungal communities were mainly shaped by development stages. The microbial α-diversities firstly increased and then decreased with plant grew, and the variation in microbial composition was active at the 3-year root growth (3YR) stage. The variation trend of cross-domain co-occurrence networks complexity was similar to the alpha-diversities. Cross-domain nodes decreased at the 3YR stage, however, fungal nodes showed an increase at the 3YR stage. In short, this study provided a detailed and systematic survey of rhizosphere microbiomes during growth stages of P. notoginseng, which revealed the development stages of Panax notoginseng drove the temporal dynamics of rhizosphere communities. This study could help us harness the power of microbiomes to evaluate herbal medicine growth, and also provide valuable information for guiding the microbial breeding of medical plants.